Unequal means more unfair means more negative emotions? Ethical concerns and emotions about an unequal distribution of negative outcomes of a local energy project. (June 2022) - Huijts, Nicole M.A.; Contzen, Nadja; Roeser, Sabine
Abstract: Emotions may play an important role in how citizens respond to public policies, and energy policies in particular. Yet, little insights exist into causes of those emotions. This study investigates ethical concerns as the basis of emotions. We test whether people perceive an unequal distribution of negative outcomes of a local energy project as more unfair than an equal distribution thereof and, in turn, experience stronger negative emotions (hypothesis 1) and whether these effects depend on whether the project has personal consequences or not (i.e. the self-relevance of the project; hypothesis 2). In an experiment with a 2 (equal vs. unequal distribution) by 2 (self-relevant vs. not self-relevant) design ( N  = 282), we find support for hypothesis 1, but not 2. Furthermore, we find that perceived total amount of harm, an ethical concern about the total amount of negative outcomes bestowed on all people together, is also (marginally significantly) affected by the unequal distribution and relates to the emotions. We argue that justified ethical concerns are at the root of emotions about renewable energy projects and therefore emotions and their underlying ethical concerns should be considered for socially responsible as well as successful energy policy making. Highlights: Renewable energy projects may cause strong (negative) emotions. Such emotions are ethically justified if they are based on ethical concerns. A project's unequal distribution of negative outcomes led to perceived unfairness. Perceived unfairness led to more negative emotions. As unfairness is an ethical concern, the emotions are ethically justified.